Impact of statewide safe sleep legislation on hospital practices and rates of sudden unexpected infant deaths - Kirsten Bechtel; Marcie Gawel; Gregory A. Vincent; Pina Violano (BMC, 2020)
Abstract Background Sudden Unexpected Infant Death (SUID) is the leading cause of death in the post-neonatal period in the United States. In 2015, Connecticut (CT) passed legislation to reduce the number of SUIDs from hazardous sleep environments requiring birthing hospitals/centers provide anticipatory guidance on safe sleep to newborn caregivers before discharge. The objective of our study was to understand the barriers and facilitators for compliance with the safe sleep legislation by birthing hospitals and to determine the effect of this legislation on SUIDs associated with unsafe sleep environments. Methods We surveyed the directors and/or educators of the 27 birthing hospitals & one birthing center in CT, about the following: 1) methods of anticipatory guidance given to parents at newborn hospital discharge; 2) knowledge about the legislation; and 3) barriers and facilitators to complying with the law. We used a voluntary online, anonymous survey. In addition, we evaluated the proportion of SUID cases presented at the CT Child Fatality Review Panel as a result of unsafe sleep environments before (2011-2015) and after implementation of the legislation (2016-2018). Chi-Square and Fisher's exact tests were used to evaluate the proportion of deaths due to Positional Asphyxia/Accident occurring before and after legislation implementation. Results All 27 birthing hospitals and the one birthing center in CT responded to the request for the method of anticipatory guidance provided to caregivers. All hospitals reported providing anticipatory guidance; the birthing center did not provide any anticipatory guidance. The materials provided by 26/27 (96%) of hospitals was consistent with the American Academy of Pediatrics (AAP) Guidelines. There was no significant change in rates of SUID in CT before (58.86/100,000) and after (55.92/100,000) the passage of the legislation (p = 0.78). However, more infants died from positional asphyxia after (20, 27.0%) than before the enactment of the law (p < 0.01). Conclusions Despite most CT hospitals providing caregivers with anticipatory guidance on safe sleep at newborn hospital discharge, SUIDs rates associated with positional asphyxia increased in CT after the passage of the legislation. The role of legislation for reducing the number of SUIDs from hazardous sleep environments should be reconsidered.